Circulating tumor cells as prognostic and predictive markers in metastatic breast cancer patients receiving first-line systemic treatment - Giuliano, Mario; Giordano, Antonio; Jackson, Summer; Hess, Kenneth R; De Giorgi, Ugo; Mego, Michal; Handy, Beverly C; Ueno, Naoto T; Alvarez, Ricardo H; De Laurentiis, Michelino; De Placido, Sabino; Valero, Vicente; et al. (Breast cancer research : BCR, 2011)
Introduction Circulating tumor cells (CTCs) represent an independent predictor of outcome in patients with metastatic breast cancer (MBC). We assessed the prognostic impact of CTCs according to different first-line systemic treatments, and explored their potential predictive value in MBC patients. Methods We retrospectively evaluated 235 newly diagnosed MBC patients, treated at the University of Texas MD Anderson Cancer Center. All patients had a baseline CTC assessment performed with CellSearch ® . Progression-free survival and overall survival were compared with the log-rank test between groups, according to CTC count (< 5 vs. ≥ 5) and type of systemic therapy. We further explored the predictive value of baseline CTCs in patients receiving different treatments. Results At a median follow-up of 18 months, the CTC count was confirmed to be a robust prognostic marker in the overall population (median progression-free survival 12.0 and 7.0 months for patients with CTC < 5 and ≥ 5, respectively; P < 0.001). Conversely, in patients with human epidermal growth factor receptor-2-overexpressed/amplified tumors receiving trastuzumab or lapatinib, the baseline CTC count was not prognostic (median progression-free survival 14.5 months for patients with CTC < 5 and 16.1 months for those with CTC ≥ 5; P = 0.947). Furthermore, in patients with human epidermal growth factor receptor-2 normal tumors, a baseline CTC count ≥ 5 identified subjects who derived benefit from more aggressive treatments, including combination chemotherapy and chemotherapy plus bevacizumab. Conclusions This analysis suggests that the prognostic information provided by CTC count may be useful in patient stratifications and therapeutic selection, particularly in the group with positive CTCs, in which various therapeutic choices may procure differential palliative benefit.